Explaining Changes in Organizational Form: The Case of Professional Baseball. (August 2016) - Hanssen, F. Andrew; Meehan, James W.; Miceli, Thomas J.
In this article, we investigate changes over time in the organization of the relationship between Major League Baseball and minor league baseball teams. We develop a model in which a minor league team serves two functions: talent development and local entertainment. The model predicts different modes of organizing the relationship between majors and minors based on the value of these parameters. We then develop a discursive history. Consistent with the model's predictions, we find that when the value of minor league baseball's training function was low but the value of its entertainment function was high, major and minor league franchises operated independently, engaging in arms'-length transactions. However, as the training function became more important and the local entertainment function less important, formal agreements ceded control of minor league functions to major league franchises. Finally, as the value of local entertainment rose once again in the late 20th century, the two roles were split, with control of local functions accruing to local ownership and training functions to major league teams. This analysis helps shed light on factors that influence the boundaries of the firm.